Clinical course of dilated cardiomyopathy in children - E., Sivakumar; P., Ramasubramaniam (International Journal of Contemporary Pediatrics, 2019)
Background: Dilated cardiomyopathy (DCM) in children is a serious disorder. Here authors study the risk factors for predicting prognosis of dilated cardiomyopathy in children. Methods: An observational case series study done in Institute of child health and research centre, Government Rajaji hospital, Madurai during September 2012 to August 2014. The diagnosis of DCM was based on clinical examination and echocardiographic evidence. Patients were followed up and grouped according to the outcome as improved or cured (group I), no change in clinical status (group II) and worsened or dead (group III). Results: 31 children less than 12 years of age were diagnosed as DCM. 13 children came under group I with a mean age of 2.15±2.5 and the mean cardiothoracic diameter ratio in chest X-ray was 59.8±3.3. The mean left ventricular ejection fraction at the time of admission was 38.7±3.04 and was 52.1±2.7 on last follow up. 11 children came under Group III with a mean age of 5.35±4.4 and the mean cardiothoracic diameter ratio was 65.3±2.7. The mean left ventricular ejection fraction was 35.8±3.7 at admission and 32.6±2.9 on last follow up. Only two children came under Group II and hence their comparison is negligible. Conclusions: Children with higher age at the time of diagnosis, higher cardiothoracic diameter ratio in chest X-ray and a low left ventricular ejection fraction on serial echocardiogram were associated with a poor outcome.